Bacteriological profile and antimicrobial susceptibility patterns of blood culture isolates among bloodstream infection suspected patients attending in a referral hospital (Bangladesh Journal of Medical Microbiology, 2021)
Bloodstream infections (BSIs) are the leading cause of morbidity and mortality in people of all ages. On time diagnosis and appropriate antimicrobial treatment is of utmost important to save the lives of affected ones. The present study is aimed to determine the bacterial profile and antimicrobial susceptibility patterns of blood culture isolates among BSI suspected patients attending in Uttara Adhunik Medical College and Hospital from 1st July to 31st December, 2020. This cross sectional study was conducted among 1,675 BSI suspected patients. About 10 ml of venous blood for adults and 2-3 ml for children was collected aseptically and transferred into an automated blood culture bottle. The BD BACTEC FX40 automated blood culture method was used to isolate bacterial pathogens and antimicrobial susceptibility test was performed by Kirby-Bauer disc diffusion method following CLSI guidelines. The rate of bacteriologically confirmed cases was 222/1675 (13%). Majority of BSI were caused by gram negative bacteria predominantly Salmonella Typhi (51%) followed by Salmonella paratyphi (15%), Escherichia coli (15%), Klebsiella spp. (7%), Staphylococcus aureus (6%), Pseudomonas aeruginosa (4%). Salmonella Typhi and Salmonella Paratyphi isolates showed 100% susceptibility to meropenem and ceftriaxone. A higher percentage of strains of Salmonella Typhi (80%,84%,85%) and Salmonella Paratyphi (93%,95%,95%) were found sensitive to amoxiclav, chloramphenicol and cotrimoxazole whereas only 4% isolates were sensitive to ciprofloxacin which is an alarming situation. None of the antibiotic was 100% effective against Escherichia coli, Klebsiella spp. and Pseudomonas aeruginosa. Amikacin and meropenem were found more effective against gram negative bacteria. In this study, none of the S. aureus strains showed resistance to cloxacillin, amoxiclav, gentamicin and doxycycline and sensitivity to azithromycin and clindamycin were found 40% and 50% respectively. Multidrug resistance among blood stream isolates are increasing in a threatening way which need to be addressed through effective surveillance and infection control strategies.Bangladesh J Med Microbiol 2021; 15 (2): 5-11